Eliminating reversible hydrogen embrittlement in high-strength martensitic steel by an electric current pulse. (1st May 2022) - Yi, Kun; Ma, Rui; Xiang, Siqi; Liu, Xuebing; Liu, Changhao; Zhang, Xinfang; Fu, Yabo
Abstract: Hydrogen embrittlement has been a great issue in ultrahigh-strength automotive steel applications. Few studies on solving hydrogen embrittlement have been conducted in terms of removing hydrogen, and most studies focus on improving the resistance to hydrogen embrittlement through microalloying. In this study, an electric pulse was used to solve hydrogen embrittlement by removing hydrogen at 120 Hz (frequency), 180 μs (duration), and 200 A (current intensity). The temperature of the samples reached 105 °C under these parameters. Compared with the samples heat treated at the same temperature, the precharged samples processed by electric pulses had a lower hydrogen content and less ductility loss. Moreover, electric pulse processing can also reduce the approximate equilibrium concentration of hydrogen compared with heat treatment. This is due to the introduction of electrical free energy, which reduces the barrier to hydrogen diffusion, and pulsed electric current also accelerates the hydrogen diffusion. Highlights: Hydrogen removal is accelerated by electropulsing to avoid hydrogen embrittlement. Electropulsing processing reduces approximate hydrogen equilibrium concentration. Electrical free energy provides a significant modification to trap binding energy. The electron wind force accelerates the diffusion of hydrogen.